Marry me [videorecording (DVD)] - Rogers, John (Screenwriter); Lopez, Jennifer, 1970-; Wilson, Owen, 1968-; Maluma, 1994-; Bradley, John, 1988-; Coleman, Chloe, 2008-; Silverman, Sarah; Ballhaus, Florian, 1965-; Crosby, Bobby, 1980- (Universal, 2022)
A betrayed pop star, slated to marry her pop star fiancée on stage, instead marries a stranger from the audience, a high school math teacher. Against the odds, their sham relationship develops into something real, but can their love survive the limelight?